From Lab to Limb: Unraveling Translational Insights and Significance of Animal Models in Lower Extremity Transplantation - Yalcin Kulahci; Naga Anvesh Kodali; Zeynep Demir; Omer Dirican; Bedreddin Sazoglu; Ramu Janarthanan; Fatih Zor; Vijay S. Gorantla (JPRAS Open)
The advancements in medicine throughout the twentieth century have been largely attributed to animal studies. The initial step in researching an animal disease is to establish a model closely resembling the clinical circumstances in humans. Consequently, an excellent animal model is essential for almost any experimental research. The aim of this review is to evaluate the current research on animal models for lower extremity transplantation (LET) and determine how pertinent and significant these models are for therapeutic settings. To bring the reader up to date from an allotransplantation standpoint, we also review, assess, and highlight the noteworthy and intriguing results of the clinical cases performed so far and various animal models. The discussion of their clinical applicability and practicality in the present and future has shed light on the experience with vascularized composite allotransplantation (VCA) around the globe.